Prevalence of Self-Medication for Oral Health Problems: A Cross Sectional Study - Khazir, Mahbooba; Nasar, Areeba; Abdullah, Sabzar; Rajput, Geeta; Amina (International Journal Of Drug Research And Dental Science, 2022)
Aim: This study was conducted to find out the prevalence of self-medication practices for oral health problems among adults attending the Institute of dental education & advance studies. All the factors like why they were using i.e reason for using the self-medication, what types of medication they were using, what was the duration of using as well as where from they get those medications i.e the source of medication were recorded.Methods: This cross-sectional study was conducted among adult patients attending the Institute of dental education & advance studies (IDEAS). After using the inclusion and exclusion criteria total of 565 subjects were included in this study. A self-administered closed-ended questionnaire was used for collecting the data. Statistical analysis was done by using SPSS software version 22.Results: Among the total 500 samples, 445 were practicing self-medication. About 26-35years mean age group was using self-medication for oral health problems and among them 51% were men and 47% were women. Although the majority (47%) of the subjects were having higher education, they were not having any medical link. The most common reason for using this method of medication was toothache (56.4%). While asking them the reasons for self-medication we got the answers like the concept of dental diseases being not so serious (36.7%) as well as time constraints for dental visits (37.5%). During our study, it was found that the most common medicine used was Analgesics.Conclusion: It was found that the use of Self-medication for oral health problems is a common practice. The concept of dental diseases being not so serious as well as constraints for dental visits being the most common reason for self Analgesics.